Reformulation of Bribery Provisions for Foreign Public Officials and International Organizations in Indonesia's Anti-Corruption Law - Susilawati, Narfin; Rahman, Andi Tenri Asniar; Imala, Jihan (Journal of Law, Politic and Humanities, 2025)
Corruption in Indonesia is a major issue, particularly in regards to bribery of foreign public officials and officials from international organizations. Corruption, being a worldwide problem, not only harms the economy but also weakens democracy and erodes public confidence. Even though Indonesia has ratified the United Nations Convention Against Corruption (UNCAC) through Law No. 7 of 2006 concerning the Ratification of the United Nations Convention Against Corruption, 2003, the laws addressing bribery of foreign public officials and officials of international organizations have not been implemented in Indonesia. This research uses a comparative approach by comparing regulations in Indonesia and France which have criminalised active and passive bribery against foreign public officials. Through the analysis of bribery cases in Indonesia, this research shows that there is a legal vacuum that results in law enforcement officers being unable to follow up on bribery perpetrators who are foreign citizens. Therefore, reforming the current laws to address bribery involving foreign public officials and international organization officials is essential in Corruption Eradication Law (UU Pemberantasan Tindak Pidana Korupsi). This study suggests the introduction of more robust regulations to enhance anti-corruption measures and uphold the integrity of the legal system in Indonesia.